KEMAMPUAN BERPIKIR KREATIF DAN PENGUASAAN KONSEP SISWA MELALUI MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN BIOLOGI KELAS XI IPA SMAN 2 PEKANBARU TAHUN AJARAN 2010/2011 - Wan Syafi’i; Evi Suryawati; Ardiyas Robi Saputra (Biogenesis, 2011)
Has been studied to determine the ability of creative thinking and mastery of the concept of students in learning biology class XI SMA Negeri 2 Pekanbaru. Research was conducted in January to March 2011 with sample student is 1 and XI IPA 2 SMA Negeri 2 Pekanbaru. This research is an experiment with a class XI IPA 1 as a classroom experiment and XI IPA 2 as the control class. The parameters used in the study of creative thinking skills and mastery of the concept of students. The result of creative thinking skills can be seen from the tests given to students in grade experiment that is equal to 69.40 with less category, while the control class at 56.60 with less category. The result of student’s mastery of concepts can also be seen from the tests given to students in grade experiment that is equal to 80.08 with a high category, while the control class at 68.29 to the medium category. Student learning outcomes can also be seen from the experimental class at 74.74 and 62.45 for the control class. Based on research that has been done, the model Problem Based Learning (PBL) in teaching biology showed better results in terms of creative thinking skills, mastery of concepts and student’s class XI IPA SMAN 2 Pekanbaru in Academic Year 2010/2011.Keywords: Creative Thinking, Concept Mastery, Problem Based Learning (PBL)